Latent tuberculosis infection detection and active tuberculosis prevention in patients receiving anti‐TNF therapy: an Italian nationwide survey. (14th July 2015) - Cantini, Fabrizio; Lubrano, Ennio; Marchesoni, Antonio; Mathieu, Alessandro; Olivieri, Ignazio; Salvarani, Carlo; Scarpa, Raffaele; Spadaro, Antonio
Abstract: Aims: Primary: to investigate Italian rheumatology practice regarding latent tubercular infection (LTBI) detection and tuberculosis (TB) prevention in patients requiring anti‐tumor necrosis factor (anti‐TNF) therapy. Secondary: to assess the overall number of TB cases over 10 years and their distribution by drug. Methods: An anonymous, 24 multiple‐response questionnaire was completed by 393/449 (87.5%) rheumatologists prescribing anti‐TNF therapy. Six questions provided setting information, and 18 the compliance with recommendations and the recorded TB cases. Results: The Italian recommendations were used by 323 (82%) and other sets by 60 (15%). TB specialists were always consulted by 81 (21%) and occasionally by 73 (19%). LTBI screening was made using chest radiograph (CR) by 5%, tuburculin skin test (TST) by 5.3%, CR + TST by 35.6%, interferon‐gamma release assay (IGRA) by 7.4%, CR + IGRAs by 26% and CR + TST + IGRA by 20.6%. Isoniazid was initiated in the presence of positivity of TST by 97 (24.7%), TST + IGRA by 101 (25.7%) and IGRA by 195 (49.6%). Anti‐TNF starting delay was 1 month in 63.1% of the cases, 3 months in 27.7%, concomitantly in 5.6%. Overall, 317 TB reactivation cases occurred in 39 353 patients, with an incidence rate of 80.5 cases/100 000/year (10 times higher than in the Italian general population). TB occurred during TB prophylaxis in 192 (60.6%). TB cases incidence rate divided by drug was: etanercept (ETN) 51 (16%), 28/100 000/year, adalimumab (ADA) 98 (31%), 89/100 000/year, infliximab (IFX) 137 (43.2%), 211/100 000/year, with a significantly lower frequency in the ETN group compared to ADA and IFX groups (χ 2  =  P  <   0.001). Conclusion: Italian rheumatologists are highly aware of anti‐TNF‐related TB risk with variable LTBI screening and TB prevention strategies. TB outcome was significantly lower in the ETN group.